2017
DOI: 10.1093/pm/pnx275
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Adult ADHD in Patients with Fibromyalgia Syndrome

Abstract: These results indicate that the co-occurrence of adult ADHD in FMS may be highly prevalent and may also significantly impact the morbidity of FMS. Patients with FMS should be assessed for the presence of adult ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 43 publications
4
13
1
Order By: Relevance
“…As expected, FM patients exhibited greater levels of childhood and adult ADHD symptoms compared with healthy controls. Higher incidence of both childhood and adult ADHD symptoms in patients with fibromyalgia in this study is in line with previous data (Golimstok, Fernandez, & Garcia Basalo, 2015;Reyero et al, 2011;Van Rensburg, Meyer, Hitchcock, & Schuler, 2017). A recent study demonstrates this symptom-based comorbidity at the clinical level as well (Yılmaz, & Tamam, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As expected, FM patients exhibited greater levels of childhood and adult ADHD symptoms compared with healthy controls. Higher incidence of both childhood and adult ADHD symptoms in patients with fibromyalgia in this study is in line with previous data (Golimstok, Fernandez, & Garcia Basalo, 2015;Reyero et al, 2011;Van Rensburg, Meyer, Hitchcock, & Schuler, 2017). A recent study demonstrates this symptom-based comorbidity at the clinical level as well (Yılmaz, & Tamam, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…In an earlier small study, patients with fibromyalgia were reported to have higher rates of ADHD symptoms both in adulthood and in childhood when compared to other pain disorder groups (Krause, Krause, Magyarosy, Ernst, & Pongratz, 1998). In a recent study, possible diagnosis of ADHD assessed by Adult ADHD Self-Report Scale in patients with fibromyalgia was more prevalent than the control group and possible ADHD comorbidity was shown to have a significant impact on disease severity (Van Rensburg, Meyer, Hitchcock, & Schuler, 2017). Childhood ADHD symptoms were also found to be more common in patients with fibromyalgia than healthy controls (Reyero et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Paying attention to ADHD in the treatment of fibromyalgia may deliver desirable clinical outcomes. 42 …”
Section: Discussionmentioning
confidence: 99%
“…These changes were not observed in the women with FM between the ST and the DT conditions. This could be derived from the attention deficit disorder ( van Rensburg et al, 2018 ; Yilmaz and Tamam, 2018 ), which is common in this population. Besides, people with FM usually showed depression or cognitive impairment ( Wolfe et al, 2010 ) in several domains such as long-term memory ( Canovas et al, 2009 ), short-term memory ( Park et al, 2001 ), or working memory ( Coppieters et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that DT would engage brain areas related to executive function (prefrontal cortex) ( Ford et al, 2002 ; Giraud et al, 2007 ) and areas related to sensorimotor integration (sensorimotor cortex and posterior parietal cortex) ( Sipp et al, 2013 ; Beurskens et al, 2016 ; Bradford et al, 2016 ). Moreover, neurophysiological differences between healthy controls and people with FM could emerge since people with FM reported an attention deficit disorder ( van Rensburg et al, 2018 ; Yilmaz and Tamam, 2018 ). This is because people with FM have impaired the ability to perform two simultaneous tasks ( Huijnen et al, 2015 ; Villafaina et al, 2018 , 2019d ).…”
Section: Introductionmentioning
confidence: 99%